Energy budgeting of aerobic rice (Oriza sativa)-wheat (Triticum aestivum) cropping system as influenced by potassium fertilization - S, VIJAYAKUMAR; KUMAR, DINESH; SHIVAY, Y S; SHARMA, V K; SHARMA, D K; P, SARAVANANE; S, POORNIMA; SINGH, NAIN (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted in 2015–16 and 2016–17 to estimate the energy budget of aerobic rice (Oriza sativa L.)-wheat (Triticum aestivum L.) cropping system (RWCS) as influenced by K fertilization. Results revealed that in aerobic RWCS the non-renewable energy and renewable energy shares 86% and 14% of the total input energy use respectively. Split application of recommended dose of K (RDK=60 kg K2O/ha) in both rice and wheat, at 50:50 or 75:25 ratio increased the system productivity by 8.2% over applying entire dose as basal (B). Among the treatments, T12 (150% RDK as basal) recorded the highest energy input (37481.5 MJ/ha), whereas T1 (control) recorded the lowest (35474.5 MJ/ha). Treatments T11 [75% RDK as basal + 25% at panicle initiation (PI) or ear initiation (EI)+ 2 foliar spray of 2.5% KNO3] recorded the highest output energy (340 ×103 MJ/ha) which remained at par with T4 [50% RDK as basal + 50% at panicle initiation (PI) or ear initiation (EI)], whereas the lowest was recorded in control (275.9 ×103 MJ/ha). Two split application of 60 kg K2O/ha at 50:50 ratio increased the system energy output by 5.5% and 13.5% over T2 (100% RDK as basal) and T3 (50% RDK as basal) respectively. Similarly, split application of potassium under T4 treatments increased the system energy use efficiency, energy productivity and energy profitability by 17.9%, 25% and 20.5% respectively over control. Thus in aerobic RWCS, 4R (right time, right dose, right method, right form) stewardship based K application ensure efficient utilization of input energy and maximize the production of biological energy.